The Exhibitions of American Art in Belgrade during the Cold War: Problem of the Relationship between Art and Politics - Mitić, Lora (Actual Problems of Theory and History of Art, 2013)
During the 5th and 6th decades of the 20th c. that were marked with the atmosphere of Cold war, Yugoslavia was shaping its political, social, cultural identity. By changing the political strategies after degrading the relations with the USSR since 1947, and by turning to the West, i.e. towards Europe and especially the US in the 1950’s, social life and culture were in a very specific and complex Yugoslav space, going through a special stadium of liberalization. Belgrade as the capital of Yugoslavia and a crucial point of the most important cultural events became the scene of many foreign, international exhibitions. Our aim is to describe two very important exhibitions of American art (1956, 1961) and to problematize the question of influences of American art on Belgrade artistic scene.
Keywords: American modernism; Abstract expressionism; Belgrade art scene; Cold war; exhibitions of American art; liberalization of culture; propaganda; reception of art